The lithospheric structure along profile Vyhne based on 2D integrated geophysical modelling (Western Carpathians, Slovakia) - DÉREROVÁ, Jana; BIELIK, Miroslav; MAKARENKO, Irina; LEGOSTAEVA, Olga; KOHÚT, Igor; BÓDI, Jozef (Contributions to Geophysics and Geodesy, 2025)
We have used 2D integrated modelling method to derive a model of the lithospheric structure along profile Vyhne located in the Western Carpathians. The algorithm determines the thermal structure of the lithosphere that is controlled by other geophysical fields, namely by heat flow, topography, gravity and geoid data. Such approach allows us to distinguish between density variations at different depths. Integrated algorithm method focuses primarily on the analysis of deeper lithospheric structure, especially on the lithosphere–asthenosphere boundary (LAB). Beneath the European Platform and the Outer Western Carpathians, the LAB is nearly horizontal, lying at depths of approximately 115–118 km. Moving toward the Inner Western Carpathians, a modest increase in lithospheric thickness becomes apparent, along with the presence of a subtly developed lithospheric root, which may represent a small remnant of the upper part of the break-off subducted lithospheric slab. Based on the computed thermal structure of the lithosphere, we established a rheological model along this profile. We determined the lithospheric strength distribution (considering both brittle and ductile deformation) for compressional and extensional settings, calculated the vertically integrated strength, and constructed the yield-strength envelope for the tectonic environment of the Vyhne tidal station. Our findings clearly indicate that a compressional regime prevails, with the greatest strength beneath the European Platform and the Western Carpathians. Along the modelled profile, strength declines from the high values observed beneath the European Platform to a minimum within the Pieniny Klippen Belt before rising again to peak values beneath the Western Carpathians.